Landscape elements as a source of floristic-structural heterogeneity of the tree component in an area of ombrophilous mixed forest Elementos da paisagem como fonte de heterogeneidade florístico-estrutural do componente arbóreo em área de floresta ombrófila mista - Spiazzi F.R.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.This study aimed to test the hypothesis that different landscape elements, such as corridors, connected and non-connected forest fragments, have a tree component with floristic-structural differences. For this sake, the tree component of a fragment-corridor system was sampled by permanent plots (10 × 20 m), totaling an area of 1.4 ha. Within the plots, tree individuals with the circumference at breast height (cbh) greater than 15.7 cm, which botanical identities were determined in the field, were sampled and counted. The landscapes metrics (fragment size area, nearest neighbor distance and edge-interior relation) were extracted from a LANDSAT image, by FRAGSTAT software. The organization and richness of the tree component in the landscape were analyzed through Non-Metric Multidimensional Scaling (NMDS), non-parametric multivariate variance analysis (NPMANOVA), Jaccard and Bray-Curtis dissimilarities indices, rarefaction, Venn diagram and indicator species analysis. Three non-connected fragments, two connected fragments and two forest corridors were recognized. In these landscape elements, a total of 84 species, 60 genera and 36 botanical families were found. The most floristically distinctive landscape element was the corridor. The hypothesis that the different landscape elements have a tree component with floristic-structural differences was accepted, supporting the idea that the spatial organization of forest fragments and corridors is relevant for the organization of tree vegetation in a landscape scale.